The Dual Nature of Stress at Work: A Challenge-Hindrance Framework Perspective - Tio Fahri Dianmas; Novi Fitria Hermiati; Alip Hanoky (Escalate : Economics and Business Journal, 2025)
This study presents a systematic literature review of 27 peer-reviewed articles published between 2013 and 2023 to critically examine the relevance and adaptability of the Challenge-Hindrance Stressor Framework (CHSF) in contemporary organizational settings. The findings reveal that while the CHSF continues to offer foundational insights into how workplace stressors influence employee outcomes, its dichotomous classification often fails to capture the contextual, perceptual, and dynamic complexities of real-world stress experiences. Factors such as leadership style, organizational justice, cultural norms, and digital transformation significantly mediate the appraisal and impact of stressors. Moreover, individual resilience and coping mechanisms emerged as crucial moderators that influence whether stressors are perceived as challenges or hindrances. The review calls for a reconceptualization of CHSF into a more integrative and fluid model that accommodates multidimensional stressor interactions and evolving work environments. This updated perspective provides a stronger theoretical and practical foundation for future research and organizational interventions aimed at improving employee well-being and performance.